Risk Assessment on STIs and HIV Transmission among Migrant Labours in Rukum District - Budathoki, HB; Devkota, GP (2016)
Background: Studies carried out in Nepal have shown a higher than average prevalence of STIs and HIV/AIDS among female sex workers, common intravenous drug users, transport workers, migrant labours compared with rest of the people. There is a scarcity of fact data about the number of migrant labours in Nepal. It is projected about 80 percent of total male independent population and 5 percent of total independent female population are being emigrated from Rukum to India either due to poor economic condition or Maoist insurgency. This study therefore focuses on assessing the risk of STIs and HIV/AIDS transmission among migrant labours in Rukum district. Methods: The study depends mainly on primary data derived from a descriptive design with clinical examination, serological testing and survey questionnaire. A total of 180 migrant labours including 172 males and 8 females were selected from different 10 VDCs of Rukum district. Data entry, processing and analysis were done in Epi-info statistical software. Results: About 15.57% of blood sampled migrant labours got affected with Syphilis. Likewise 7.78% and 1.16% of blood sample had fallen under Gonorrhoea and Trichomonas Vaginalis respectively. Most of them were infected with multiple infections like Syphilis and Gonorrhoea. Among the blood sampled populace, one was found to be infected with HIV/AIDS. Risk factors associated with transmission of STIs and HIV/AIDS were less use of condom, poverty, Maoist insurgency, isolation from their life partners, high intension of sexual arousal keeping secret of STIs and HIV/AIDS problems, lack of knowledge about the modes of transmission and preventive measures, not following medical treatment, lack of personal hygiene and sanitation etc. Conclusions: Syphilis, Gonorrhoea and Trichomonas are still common than HIV infections and there is low prevalence of HIV infection in population of Rukum. However non-recognition of condom use as proper way to protect onself against HIV/AIDS put the population at risk of greater epidemic. Keywords: gonorrhea; HIV/AIDS; migrant labours; prevalence; risk; syphilis; trichomonas vaginalis.